Analisis Kebijakan Pemerintah Kota Jambi Terhadap Kerjasama Internasional Daerah - Ahmad Baidawi; Iswandi Iswandi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
This study aims to analyze Jambi City government policies towards regional international cooperation and explain the authority of local governments in cooperating with foreign parties through international agreements in the context of the Unitary State of the Republic of Indonesia and to examine the implementation of international agreements made by local governments as a form of autonomy. area. This research was conducted using qualitative and normative juridical research methods. The type of data used consists of primary data, secondary data, tertiary data. Data collection was carried out through observation, interviews and literature study. All data collected were analyzed using qualitative descriptive methods. The results of the interim research show that the local government of the city of Jambi has carried out various international collaborations in various fields. However, the policies taken towards international cooperation have not been maximal. In addition, local governments are also given the authority to be able to carry out international cooperation with foreign parties. This international cooperation uses international treaty instruments. This collaboration aims to empower regional potential, improve public services, and improve the welfare of local communities, especially those in the city of Jambi. The purpose of this International Cooperation is to create opportunities for local communities to take part in taking part in the regional development process. One form of cooperation is through the sister city and sister province.